HUBUNGAN POWER OTOT TUNGKAI DAN KELENTUKAN OTOT PUNGGUNG DENGAN HASIL SMASH PADA TIM BOLAVOLI PUTRA SMAN OLAHRAGA PEKANBARU - Rapita, Rapita; Ramadi, Ramadi; Nita Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on the observation that researchers did on team volleyball Sport SMAN Soweto student son, still a lot of players who have experienced failure at the time did smash volleyball. Failure often occurs when smash such as: ball nyangkut dinet, the ball can be returned or diblock by the opponent, the ball is not right on target or diblock by opponents is seen at the time of the team doing the exercises and games. It allegedly contributing factor is the physical condition of athletes. Ujuan in this research is to know the relationship power oto kelentukan limb and back muscles with the results smash in a volleyball Jock son Sport SMAN Pekanbaru. The population in this research is the entire volleyball athlete son SMAN the Soweto Sports Team volleyball Sport SMAN totalling 12. The sample in this study were 12 people using total sampling. Instrument in this study are the vertical jump test, brig up (kayang) and the resulting smash. The data obtained in the analysis by using correlation product moment. On the basis of the research results obtained from results obtained power limb muscles have no relationship with the precision of the Smash in a volleyball Jock son Sport SMAN Pekanbaru. From the results obtained kelentukan back muscles have no relationship with the precision of the Smash in a volleyball Jock son Sport SMAN Pekanbaru. There is no relationship between power simultaneously limb muscles and back muscles against precision kelentukan Smash volleyball athletes in Sport SMAN son of Soweto.Keywords: Power Oto Kelentukan Limbs, Back Muscles, The Results Smash